Method for Producing Porous Articles from Ultra-High Molecular Weight Polyethylene

JP2025506187AActive Publication Date: 2025-03-07WL GORE & ASSOC INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024547696
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-14
Filing Date
2023-02-13
Publication Date
2025-03-07
Estimated Expiration
2043-02-13

Smart Images

  • Figure 2025506187000001_ABST
    Figure 2025506187000001_ABST
Patent Text Reader

Abstract

An ultra-high molecular weight polyethylene (UHMWPE) polymer is provided having an average molecular weight of at least 2,000,000 g / mol and an enthalpy of at least 190 J / g. The UHMWPE polymer can include at least one comonomer. The UHMWPE polymer is used to form a membrane, which when stretched has a node and fibril structure. The UHMWPE membrane has an endotherm of about 150° C. associated with the fibrils in the membrane. The membrane has a porosity of at least 60% and a bubble point of 138 kPa or less. Additionally, the UHMWPE membrane has a thickness of less than 1 mm. The UHMWPE membrane can be formed by lubricating the UHMWPE polymer, subjecting the lubricated polymer to pressure at a temperature below the melting point of the UHMWPE polymer to form a tape, and stretching the tape at both temperatures below and above the melting temperature of the UHMWPE polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of Provisional Application No. 63 / 309,891, filed February 14, 2022, the contents of which are incorporated herein by reference for all purposes.

[0002] The present disclosure relates generally to ultra-high molecular weight polyethylene (UHMWPE) polymers, and more specifically to methods of forming porous articles from highly crystalline ultra-high molecular weight polyethylene polymers. [Background technology]

[0003] Ultra-high molecular weight polyethylene is well known in the art. Articles made from ultra-high molecular weight polyethylene have properties such as toughness, impact strength, abrasion resistance, low coefficient of friction, gamma resistance, and resistance to attack by solvents and corrosive chemicals. Due to the favorable attributes associated with ultra-high molecular weight polyethylene, it has been utilized in a variety of applications such as load-bearing components of joint prostheses, vibration damping pads, hydraulic cylinders, sports equipment (including, but not limited to, skis, ski poles, goggle frames, protective helmets, and climbing equipment), and specialized applications in aerospace.

[0004] UHMWPE polymers can be processed by compression molding, ram extrusion, gel spinning, and sintering. However, some conventional processes have one or more undesirable characteristics or attributes, such as requiring high levels of solvent, having a non-porous structure, and / or being costly or time-consuming to process due to the high viscosity of the UHMWPE polymer. Thus, there is a need in the art for a method of producing UHMWPE articles that are processed at temperatures above the melting temperature of the UHMWPE polymer, have high strength, a node and fibril microstructure for ease of processing, and are highly porous. Summary of the Invention

[0005] Provided herein are articles comprising porous polyethylene membranes formed from ultra-high molecular weight polyethylene (UHMWPE) polymers, and methods of forming porous articles from highly crystalline ultra-high molecular weight polyethylene polymers.

[0006] According to a first embodiment ("Embodiment 1"), an article is provided that includes a porous polyethylene membrane formed from an ultra high molecular weight polyethylene (UHMWPE) polymer having a molecular weight of at least 2,000,000 g / mol and a melting enthalpy of at least 190 J / g, wherein the porous polyethylene membrane has a node and fibril microstructure having a structure of nodes interconnected by fibrils, a detectable first endotherm associated with the UHMWPE polymer in the range of 139°C to 143°C, a detectable second endotherm associated with the fibrils between 145°C to 155°C, and a bubble point of about 138 kPa or less, preferably 69 kPa or less, and more preferably 34.5 kPa or less.

[0007] Embodiment 2 is the article of embodiment 1, wherein the porous polyethylene membrane is 2.99 cm 2 has an ATEQ® airflow of at least 50 L / hr, preferably at least 500 L / hr, more preferably at least 1000 L / hr at a pressure of 1.2 kPa over a surface area of

[0008] Embodiment 3 is the article of embodiments 1-2, wherein the porous polyethylene membrane has a machine direction (MD) matrix tensile strength of at least 30 MPa.

[0009] Embodiment 4 is the article of embodiments 1-3, wherein the porous polyethylene membrane has a transverse direction (TD) matrix tensile strength of at least 4 MPa.

[0010] Embodiment 5 is the article of embodiments 1-4, wherein the membrane is biaxially oriented.

[0011] Embodiment 6 is the article of embodiments 1-5, wherein the matrix tensile strength ratio MD:TD is from about 0.1:1 to 1:0.1.

[0012] Embodiment 7 is the article of embodiments 1-6, wherein the UHMWPE polymer has a molecular weight between 2,000,000 g / mol and 12,000,000 g / mol.

[0013] Embodiment 8 is the article of embodiments 1-7, wherein the article is a sheet, membrane, tape, fiber, tube, bead, or three-dimensional free-standing structure.

[0014] Embodiment 9 is the article of embodiments 1-8, wherein the porous membrane has a porosity of at least 60%.

[0015] Embodiment 10 is the article of embodiments 1-9, wherein the membrane has an average thickness of less than 1 mm.

[0016] Embodiment 11 is the article of embodiments 1-10, wherein the UHMWPE polymer comprises 0.001 mol % to 10 mol % of a comonomer.

[0017] According to a twelfth embodiment ("Embodiment 12"), there is provided a method including lubricating an ultra-high molecular weight polyethylene (UHMWPE) polymer having a molecular weight of at least 2,000,000 g / mol and only a single endotherm with a melting enthalpy of at least 190 J / g to form a lubricated polymer, exposing the lubricated UHMWPE polymer to a pressure at a temperature below the melting temperature of the UHMWPE polymer to form a tape, stretching the tape at a temperature below the melting temperature of the UHMWPE polymer to form a stretched tape, and stretching the stretched tape at a temperature above the melting temperature of the UHMWPE polymer to form a porous UHMWPE membrane having a structure of nodes interconnected by fibrils.

[0018] Example 13 is the method of example 12, wherein the ultra high molecular weight polyethylene (UHMWPE) polymer has a molecular weight of 2,000,000 to 12,000,000 g / mol.

[0019] Example 14 is the method of example 12 or 13, wherein the porous UHMWPE membrane has a first endotherm and a second endotherm at 145° C. to 155° C. associated with fibrils in the porous UHMWPE membrane and above the melting temperature of the ultra high molecular weight polyethylene polymer.

[0020] In a fifteenth embodiment, the method of any one of the twelfth to fourteenth embodiments is characterized in that the porous UHMWPE membrane has a bubble point of 138 kPa or less, preferably 69 kPa or less, and more preferably 34.5 kPa or less.

[0021] Embodiment 16 is the method of embodiments 12-15, wherein the porous UHMWPE membrane is 2.99 cm 2 has an ATEQ® airflow of at least 50 L / hr at a pressure of 1.2 kPa over a surface area of

[0022] Embodiment 17 is the method of embodiments 12-16, wherein the tape and stretched tape are biaxially stretched, uniaxially stretched, radially stretched, or a combination thereof.

[0023] Embodiment 18 is the method of embodiments 12-17, wherein the tape is stretched at a temperature of 110°C to 135°C.

[0024] Embodiment 19 is the method of embodiments 12-18, wherein the tape is stretched at a temperature of 140°C to 170°C.

[0025] Embodiment 20 is the method of embodiments 12-19, wherein the exposing comprises calendering the lubricated UHMWPE polymer at a temperature below the melting temperature of the UHMWPE polymer to form a tape.

[0026] Example 21 is the method of embodiments 12-20, including removing lubricant from the tape before stretching.

[0027] Embodiment 22 is the method of embodiments 12-21, wherein the UHMWPE polymer has a molecular weight of 5,000,000 g / mol to 12,000,000 g / mol.

[0028] Example 23 is the method of any one of embodiments 12-22, wherein the UHMWPE membrane has a porosity greater than 60%.

[0029] Embodiment 24 is the method of embodiments 12-23, wherein the UHMWPE membrane has a first endotherm associated with the UHMWPE polymer in the range of 139°C to 143°C.

[0030] Embodiment 25 is the method of embodiments 12-24, wherein the UHMWPE membrane has an average thickness of less than 1 mm.

[0031] Embodiment 26 is the method of embodiments 12-25, wherein the UHMWPE polymer comprises 0.001 mol % to 10 mol % of a comonomer.

[0032] According to a twenty-seventh embodiment, there is provided a method comprising exposing a lubricated ultra-high molecular weight polyethylene (UHMWPE) polymer having a molecular weight of at least 2,000,000 and a first endotherm with a melting enthalpy of at least 190 J / g to pressure and heat below a first melting temperature of said UHMWPE polymer to form a preform, subsequently stretching said preform at a temperature below the melting temperature of said UHMWPE polymer to form a stretched preform, and then stretching said stretched preform at a temperature above the melting temperature of said UHMWPE polymer to form a porous UHMWPE membrane, wherein said porous UHMWPE membrane has a bubble point of 138 kPa or less, preferably 69 kPa or less, more preferably 34.5 kPa or less, and wherein said porous UHMWPE membrane has a bubble point of 2.99 cm or less. 2 has an ATEQ® airflow of at least 50 L / hr at a pressure of 1.2 kPa over a surface area of

[0033] Embodiment 28 is the method of embodiment 27, wherein the porous UHMWPE membrane has a second endotherm between 145° C. and 155° C. associated with fibrils within the porous UHMWPE membrane, the second endotherm being above the melting temperature of the UHMWPE polymer.

[0034] Embodiment 29 is the method of embodiment 27 or 28, wherein the preform and the stretched preform are biaxially stretched, uniaxially stretched, radially stretched, or a combination thereof.

[0035] Embodiment 30 is the method of embodiments 27-29, wherein the preform is stretched at a temperature of about 110°C to about 135°C.

[0036] Embodiment 31 is the method of embodiments 27-30, wherein the preform is stretched at a temperature of 140°C to 170°C.

[0037] Example 32 is the method of any of Examples 27-31, wherein the exposing comprises calendering the lubricated UHMWPE polymer at a temperature below the melting temperature of the UHMWPE polymer to form a preform.

[0038] Example 33 is the method of any of embodiments 27-32, including removing lubricant from the preform before stretching.

[0039] Embodiment 34 is the method of embodiments 27-33, wherein the UHMWPE polymer has a molecular weight of 2,000,000 g / mol to 12,000,000 g / mol.

[0040] Example 35 is the method of any one of embodiments 27-34, wherein the UHMWPE membrane has a porosity greater than 60%.

[0041] Embodiment 36 is the method of embodiments 27-35, wherein the UHMWPE membrane has a first endotherm associated with the UHMWPE polymer in the range of 139°C to 143°C.

[0042] Embodiment 37 is the method of embodiments 27-36, wherein the UHMWPE membrane has an average thickness of less than 1 mm.

[0043] Embodiment 38 is the method of any one of embodiments 27-37, wherein the UHMWPE polymer comprises 0.001 mol % to 10 mol % of a comonomer.

[0044] The foregoing embodiments are provided by way of example and should not be construed as limiting or narrowing the scope of any of the inventive concepts otherwise provided by this disclosure. While multiple examples are disclosed, still other embodiments will become apparent to those skilled in the art from the following detailed description, which shows and describes illustrative examples. Accordingly, the drawings and detailed description should be regarded as illustrative in nature and not restrictive. [Brief description of the drawings]

[0045] The accompanying drawings are included to provide a further understanding of the disclosure, and are incorporated in and constitute a part of this specification, illustrating embodiments and, together with the description, serve to explain the principles of the disclosure.

[0046] [Figure 1] FIG. 1 is a scanning electron micrograph (SEM) taken at 1,000x magnification of the surface of the expanded UHMWPE membrane of Example 1a.

[0047] [Diagram 2] FIG. 2 is a scanning electron micrograph (SEM) taken at 1,000x magnification of the surface of the expanded UHMWPE membrane of Example 1b.

[0048] [Diagram 3] FIG. 3 is a scanning electron micrograph (SEM) taken at 100x magnification of the surface of the expanded UHMWPE membrane of Example 2a.

[0049] [Figure 4]FIG. 4 is a scanning electron micrograph (SEM) taken at 100x magnification of the surface of the expanded UHMWPE membrane of Example 2b.

[0050] [Diagram 5] FIG. 5 is a scanning electron micrograph (SEM) of the surface of the expanded UHMWPE membrane of Comparative Example A taken at 1,000 times magnification.

[0051] [Figure 6] FIG. 6 is a scanning electron micrograph (SEM) of the surface of the expanded UHMWPE membrane of Comparative Example B taken at 1,000 times magnification.

[0052] [Figure 7] FIG. 7 is a differential scanning calorimetry (DSC) thermogram of the UHMWPE powder of all the examples described herein, showing an enthalpy of fusion of 232.9 J / g.

[0053] [Figure 8] FIG. 8 is a differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the expanded UHMWPE membrane of Example 1a.

[0054] [Figure 9] FIG. 9 is a differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the expanded UHMWPE membrane of Example 1b.

[0055] [Figure 10] FIG. 10 is a differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the expanded UHMWPE membrane of Example 2a.

[0056] [Figure 11] FIG. 11 is a differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the expanded UHMWPE membrane of Example 2b.

[0057] [Figure 12]FIG. 12 is a differential scanning calorimetry (DSC) thermogram showing two distinct melting points associated with the expanded UHMWPE membrane of Comparative Example A.

[0058] [Figure 13] FIG. 13 is a differential scanning calorimetry (DSC) thermogram showing two distinct melting points associated with the expanded UHMWPE membrane of Comparative Example B.

[0059] [Figure 14] FIG. 14 is a differential scanning calorimetry (DSC) thermogram showing a single melting point typical of a conventional UHMWPE membrane. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0060] Definitions and Terminology

[0061] The present disclosure is not to be construed in a limiting sense, and for example, the terms used in this application should be interpreted broadly with respect to the meaning that one of ordinary skill in the art would give such terms.

[0062] With respect to the term imprecision, the terms "about" and "approximately" may be used interchangeably to refer to measurements that include the stated measurement and also include measurements that are reasonably close to the stated measurement. Measurements that are reasonably close to the stated measurement deviate from the stated measurement by a reasonably small amount, as understood and readily ascertained by one of ordinary skill in the relevant art. Such deviations may result, for example, from measurement errors, differences in calibration of measuring and / or manufacturing equipment, human error in reading and / or setting measurements, small adjustments made to optimize performance and / or construction parameters to account for differences in measurements associated with other components, specific implementation scenarios, imprecise adjustment and / or manipulation of objects by humans or machines, and / or the like. In cases where it is determined that such reasonably small difference values ​​are not readily ascertainable by one of ordinary skill in the art, the terms "about" and "approximately" may be understood to mean plus or minus 10% of the stated value.

[0063] Description of Various Embodiments

[0064] Those skilled in the art will readily appreciate that the various aspects of the present disclosure may be implemented by any number of methods and devices configured to perform the intended functions. It should also be noted that the accompanying drawings referenced herein are not necessarily drawn to scale and may be exaggerated to illustrate various aspects of the present disclosure, and in that regard, the drawings should not be construed as limiting.

[0065] The present disclosure relates to articles including porous membranes formed from highly crystalline ultra high molecular weight polyethylene (UHMWPE) polymers having an average molecular weight (Mw) of at least 2,000,000 g / mol, or at least 3,000,000 g / mol, or at least 4,000,000 g / mol, or at least 5,000,000 g / mol, or at least 6,000,000 g / mol, or at least 7,000,000 g / mol. In exemplary embodiments, the UHMWPE polymer can have an average molecular weight in the range of 2,000,000 g / mol to 12,000,000 g / mol, or 2,000,000 g / mol to 10,000,000 g / mol, or 4,000,000 g / mol to 10,000,000 g / mol, or 5,000,000 g / mol to 8,000,000 g / mol, or any other range encompassed by these endpoints.

[0066] The article can be a sheet, film, tape, fiber, tube, or three-dimensional free-standing structure, hi an exemplary embodiment, the article is a tape.

[0067] The crystallinity of the UHMWPE polymer can be measured by differential scanning calorimetry (DSC). The UHMWPE polymer has a first melting enthalpy of at least about 190 J / g. As used herein, the phrase "high crystallinity" or "highly crystalline" is intended to describe a UHMWPE polymer having a first melting enthalpy of greater than 190 J / g as measured by DSC. In another embodiment, the UHMWPE polymer has a first melting enthalpy of greater than 195 J / g, 200 J / g, 205 J / g, 210 J / g, 215 J / g, 220 J / g, 225 J / g, or 230 J / g.

[0068] Furthermore, the UHMWPE polymer can be a homopolymer of ethylene or a copolymer of ethylene and at least one comonomer. Suitable comonomers that can be used to form the UHMWPE copolymer include, but are not limited to, α-olefins or cyclic olefins having 3 to 20 carbon atoms. Non-limiting examples of suitable comonomers include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, cyclohexene, and dienes having up to 20 carbon atoms (e.g., butadiene or 1,4-hexadiene). The comonomer can be present in the UHMWPE copolymer in an amount ranging from about 0.001 mol % to about 10 mol %, from about 0.01 mol % to about 5 mol %, from about 0.1 mol % to about 1 mol %, or any other amount included within these endpoints.

[0069] Additionally, the ultra high molecular weight polyethylene, UHMWPE polymer of the present invention has a melting point of about 139°C to about 143°C. It should be noted that the terms "melting temperature", "melting temperature" and "melting point" may be used interchangeably herein. In at least one exemplary embodiment, the UHMWPE polymer has a melting point of approximately 140°C. Subsequent remelting of the UHMWPE polymer occurs at a temperature of about 127°C to about 137°C.

[0070] When the UHMWPE polymer is formed into a membrane, the expanded UHMWPE membrane can have a node and fibril structure, as seen in Figures 1-4. Node as defined herein is intended to describe the connection point of at least two fibrils. Additionally, the UHMWPE membrane can have an endotherm at about 145°C to about 155°C, or about 150°C, associated with the fibrils within the membrane. Differential scanning calorimetry (DSC) can be used to identify the melting temperature (crystalline phase) of the UHMWPE polymer. Figure 8 shows a DSC thermograph of an exemplary UHMWPE membrane with a depressed melting temperature at about 132°C and an endotherm at about 152°C. This peak (or endotherm) at about 150°C indicates the presence of fibrils in the expanded UHMWPE membrane. It should be understood that the endothermic peak at about 150° C. is absent in conventional treated porous UHMWPE membranes, but is present in the UHMWPE membranes described, for example, in UHMWPE membranes described in U.S. Patent No. 9,926,416. A DSC thermogram of a conventional UHMWPE membrane is shown in FIG. 14, which shows a single melting peak (melting temperature) at about 134° C.

[0071] Membranes formed from UHMWPE polymers can have a percent porosity of about 60% or more, about 65% or more, about 70% or more, about 75% or more, about 80% or more, about 85% or more, about 90% or more. In exemplary embodiments, membranes formed from UHMWPE polymers can have a percent porosity of about 25% to about 90%, about 40% to about 90%, about 50% to about 90%, about 60% to about 90%, or any percent porosity subsumed between these endpoints.

[0072] Membranes formed from UHMWPE polymers can have a bubble point of about 138 kPa or less, about 100 kPa or less, about 69.0 kPa or less, about 50 kPa or less, about 34.5 kPa or less, about 20 kPa or less, about 10 kPa or less, about 8 kPa or less, about 7 kPa or less, about 6 kPa or less, about 5 kPa or less, about 4 kPa or less, about 3 kPa or less, about 2 kPa or less, or about 1 kPa or less. In exemplary embodiments, the membranes can have a bubble point of about 1 kPa to about 138 kPa, about 2 kPa to about 100 kPa, or about 3 kPa to 10 kPa, or can have a bubble point falling within these ranges.

[0073] The membrane formed from UHMWPE polymer has a surface area of ​​2.99 cm 2 At least about 50 L / hr at a pressure of 1.2 kPa over a surface area of ​​2.99 cm 2 at least about 70 L / hr at a pressure of 1.2 kPa over a surface area of ​​2.99 cm 2 at least about 100 L / hr at a pressure of 1.2 kPa over a surface area of ​​2.99 cm 2 at least about 500 L / hr at a pressure of 1.2 kPa over a surface area of ​​2.99 cm 2 at least about 1000 L / hr at a pressure of 1.2 kPa over a surface area of ​​2.99 cm 2 at least about 2000 L / hr at a pressure of 1.2 kPa over a surface area of ​​2.99 cm 2 At least about 3000 L / hr at a pressure of 1.2 kPa over a surface area of ​​2.99 cm 2 In an exemplary embodiment, the membrane has a surface area of ​​2.99 cm. 2 Approximately 50 L / hour to approximately 4000 L / hour at a pressure of 1.2 kPa, with a surface area of ​​2.99 cm 2 Approximately 100 L / hr to approximately 3000 L / hr at a pressure of 1.2 kPa or a surface area of ​​2.99 cm 2 The ATEQ can have an air flow of about 1000 L / hr to about 2000 L / hr at a pressure of 1.2 kPa over a range.

[0074] Membranes formed from UHMWPE polymers can have a matrix tensile strength (MTS) in the machine direction (MD) of at least about 30 MPa, at least about 50 MPa, at least about 100 MPa, at least about 150 MPa, or at least about 200 MPa. In exemplary embodiments, the membranes can have a matrix tensile strength in the machine direction of about 30 MPa to about 200 MPa, about 50 MPa to about 100 MPa, or about 30 MPa to about 100 MPa.

[0075] Membranes formed from UHMWPE polymers can have a matrix tensile strength (MTS) in the transverse direction (TD) (orthogonal to MD) of at least about 4 MPa, at least about 10 MPa, at least about 50 MPa, or at least about 100 MPa. In exemplary embodiments, the membranes can have a matrix tensile strength in the transverse direction of from about 4 MPa to about 100 MPa, or from about 50 MPa to about 100 MPa.

[0076] Membranes formed from UHMWPE polymers can have a matrix tensile strength ratio, determined as MD:TD, of about 0.1:1 to 1:0.1, or about 0.5:1 to 1:0.5, or about 0.7:1 to 1:0.7.

[0077] Membranes formed from UHMWPE polymers can have an average thickness of less than about 1 mm, or less than about 0.75 mm, or less than about 0.5 mm, or less than about 0.25 mm, or less than about 0.09 mm, or less than about 0.08 mm, or less than about 0.07 mm, or less than about 0.06 mm, or less than about 0.05 mm. In exemplary embodiments, the membranes can have a thickness of about 0.005 mm to about 1 mm, or about 0.01 mm to about 1 mm, or about 0.03 mm to about 1 mm, or about 0.05 mm to about 1 mm, or about 0.08 to about 0.5 mm, or any thickness within these ranges.

[0078] Membranes formed from UHMWPE polymers can have a maximum pore size (calculated based on bubble point) of about 30 μm or less, or about 25 μm or less, or about 20 μm or less, or about 15 μm or less, or about 10 μm or less. In exemplary embodiments, the maximum pore size ranges from about 0.5 μm to about 30 μm, or from about 0.5 μm to about 25 μm, or from about 0.5 μm to about 20 μm.

[0079] The UHMWPE polymers described herein can be produced by a polymerization process in which ethylene, optionally modified or slightly modified, optionally in the presence of a comonomer, is polymerized in the presence of a polymerization catalyst at a temperature below the crystallization temperature of the polymer. Such polymerization causes the polymer to crystallize immediately after production. More specifically, the reaction conditions are selected such that the polymerization rate is lower than the crystallization rate. Such synthesis conditions cause the molecular chains to crystallize immediately after production, resulting in a morphology different from that obtained by solution or melt. It should be noted that the crystalline morphology produced at the surface of the catalyst depends on the ratio of the crystallization rate to the growth of the polymer. Moreover, the synthesis temperature, which in this case is also the crystallization temperature, affects the morphology of the UHMWPE polymer thus obtained. In the UHMWPE polymer, its particle size, shape and distribution are important in order to obtain the desired porous structure. These particle characteristics affect the packing and connection density and thereby the porous structure that can be produced from the particles.

[0080] The UHMWPE resin may be provided in particulate form, for example in the form of a powder. The UHMWPE powder may be formed from individual particles having a particle size of less than about 100 nm. Typically, the powder is provided as clusters of particles having a size of about 5 to about 250 microns or about 10 to about 200 microns. In an exemplary embodiment, the clusters may have a size as small as possible, up to and including individual particles.

[0081] In forming a porous article from UHMWPE polymer, the UHMWPE polymer is first mixed with a lubricant such as light mineral oil. Other suitable lubricants include aliphatic, aromatic, halogenated hydrocarbons, etc., selected according to flammability, evaporation rate, and economic considerations. It should be understood that the term "lubricant" as used herein is intended to describe a processing aid consisting of an incompressible fluid that is not a solvent for the polymer at the process conditions. The interaction of the fluid with the surface of the polymer is such that a homogenous mixture can be created. It should also be noted that the choice of lubricant is not particularly limited, and the choice of lubricant is primarily a matter of safety and convenience. The lubricant can be added to the UHMWPE polymer in a ratio of 1 ml / 100 g to about 100 ml / 100 g or about 10 ml / 100 g to about 70 ml / 100 g. In one embodiment, the lubricant is added and the mixture is maintained at a temperature below the melting temperature of the UHMWPE polymer for a time sufficient to wet the interior of the polymer clusters with the lubricant (i.e., the holding time). "Sufficient time" may be described as time sufficient for the particles to return to a free-flowing powder. In another embodiment, the lubricant is added to the UHMWPE polymer and mixed, and the mixture is free-flowing and does not require a holding time.

[0082] After the lubricant is uniformly distributed on the surface of the particles (e.g., after it has wetted the interior of the clusters), the mixture returns to a free-flowing powder-like state. In an exemplary embodiment, the mixture is heated to a temperature below the melting temperature of the UHMWPE polymer or the boiling point of the lubricant, whichever is lower. It should be understood that various times and temperatures can be used to wet the polymer, as long as there is enough time for the lubricant to adequately wet the interior of the clusters.

[0083] Once lubricated, the particles can be processed into a solid shape or preform without exceeding the melting temperature of the polymer. In an exemplary embodiment, the preform can be a fiber, tube, tape, sheet, bead, or a three-dimensional free-standing structure. The lubricated particles are heated to a temperature below the melting temperature of the polymer and subjected to sufficient pressure and shear to form connections between the particles and create a solid shape. Non-limiting examples of methods for applying pressure and shear include ram extrusion (typically called paste extrusion or paste processing when a lubricant is present) and optional calendering.

[0084] In an exemplary embodiment, the lubricated UHMWPE polymer is calendered to produce a cohesive flexible tape. As used herein, the term "cohesive" is intended to describe a tape that is strong enough for further processing. Calendering is performed at about 115°C to about 135°C or about 120°C to about 130°C. The tape formed is of variable length and less than about 1 mm thick. Tapes can be formed that are about 0.01 mm to about 1 mm thick, about 0.08 mm to about 0.5 mm thick, or 0.05 mm to 0.2 mm thick, or even thinner. In an exemplary embodiment, the tape is about 0.05 mm to about 0.2 mm thick.

[0085] In a subsequent step, the lubricant can be removed from the tape. In the case where mineral oil is used as the lubricant, the lubricant can be removed by washing the tape with hexane or other suitable solvent. The washing solvent is selected to have good solubility for the lubricant and sufficient volatility to be removed below the melting point of the resin. If the lubricant is sufficiently volatile, the lubricant can be removed without a washing step or can be removed by heat and / or vacuum. The tape can then be optionally dried, typically by air drying. However, any conventional drying method can be used as long as the heating temperature of the sample is below the melting point of the UHMWPE polymer.

[0086] The first melting temperature of the highly crystalline UHMWPE polymer, i.e., about 139°C to about 143°C, is irreversible in that the subsequent melting and recrystallization occurs at a temperature (second melting temperature) lower than the first melting temperature. The second melting temperature of the UHMWPE polymer is about 127°C to about 137°C. A unique feature of some embodiments of the present invention is that the higher first melting temperature can be retained in the final porous article. Furthermore, the DSC of the UHMWPE membrane of the present invention has the surprising feature that the UHMWPE membrane of the present invention shows an endotherm at about 150°C associated with fibrils, which is a higher temperature than the melting temperature associated with the original UHMWPE polymer before processing.

[0087] Once the tape is dry, it is cut to a size suitable for stretching. Stretching of these samples is performed in two temperature regions: 1) below the melting temperature of the UHMWPE polymer, about 110°C to about 135°C or about 125°C to about 130°C, or 2) above the melting temperature of the UHMWPE polymer, about 140°C to about 170°C, or about 150°C to about 160°C. The samples can be stretched in one or more directions to form a porous membrane. Uniaxial or biaxial stretching can be performed at rates up to 20,000% / sec, or about 0.1% to 20,000% / sec. It has been observed that in processes performed below the melting temperature, strength increases simultaneously with stretching. In general, the strength of the polymer matrix depends on the tape strength before stretching, the quality of the resin (e.g., particle size, molecular weight, distribution of particle size and / or molecular weight, crystallinity, composition of the polymer, etc.), the temperature at which stretching is performed, the stretching speed, and the total amount of stretching.

[0088] Stretched membranes have a structure of nodes interconnected by fibrils, as seen in Figures 1-4. The porous microstructure of stretched membranes is affected by the temperature and speed of stretching. The shape of the nodes and fibrils can be controlled by resin selection, stretching speed, stretching temperature, and final stretch ratio. Membranes that are first stretched below the melting temperature of the UHMWPE polymer and then stretched above the melting temperature of the UHMWPE polymer tend to have larger nodes and larger void spaces separated by fewer interconnected fibrils.

[0089] Test Method Although specific methods and apparatus are described below, it should be understood that any method or apparatus deemed suitable by one of ordinary skill in the art may be used instead. For characterization purposes, two 17.8 cm x 17.8 cm square pieces of material were used.

[0090] Contact thickness measurement Thickness was measured by placing the sample flat on a granite block and using a manual Mitutoyo thickness gauge (Mitutoyo Corporation, Kawasaki, Japan) with a 6.35 mm metal plate. The average and standard deviation of three measurements were used for the percent porosity calculations described below.

[0091] Percent Porosity Calculation The full density of the sample is 0.94g / cm 3 The density was used to calculate the percent porosity of the stretched material using the formula: Samples were die cut and weighed using a balance. This data and the measured thickness were used to calculate the density of the membrane according to the following formula:

number

number

[0092] Matrix Tensile Strength (MTS) ASTM D412-Dog Bone Die Type F (D412F) was used to cut the samples in the longitudinal and transverse directions, respectively. The tensile break load was measured using an INSTRON 5500R tensile tester (Illinois Tool Works Inc., Norwood, MA) equipped with flat-face grips and a 500N load cell. The gauge length was 19 mm and the crosshead speed was 20.3 cm / min. For the longitudinal MTS measurements, the larger dimension of the sample was oriented in the calender direction and was designated the "machine direction" (MD). For the transverse MTS measurements, the larger dimension of the sample was oriented perpendicular to the calender direction and was designated the "transverse direction" (TD).

[0093] The sample obtained from the density measurement was used for tensile testing. The sample dimensions were 50.8mmx12.7mm. The effective thickness was calculated from the mass, area and density of the sample. Two samples were then tested individually in a tensile tester. The average of the two maximum load (i.e. peak force) measurements was reported. The longitudinal and transverse MTS were calculated using the following formulas: MTS = (maximum load / cross-sectional area)*(density of UHMWPE) / (density of sample) In the above formula, the density of UHMWPE is taken as 0.94 g / cc.

[0094] Bubble Point Measurement Bubble point pressure was measured using a Sprint iQ multifunction leak and flow tester (Uson LP, Houston, TX) following the general teachings of ASTM F31 6-03. The sample membrane was placed in the sample chamber and wetted with 100% isopropyl alcohol with a surface tension of 21.7 dynes / cm to fill the pores of the sample. The sample was then secured with a 20 mm diameter O-ring to seal the membrane against the porous metal surface. Starting with an initial pressure of 0 psi, air pressure was applied to one side of the sample and increased at 0.05 psi / min until a pressure increase of 0.20 psi was measured on the other side of the sample. This pressure is the bubble point, i.e., the air pressure required to displace isopropyl alcohol from the largest pore of the specimen. The reported values ​​represent the average and standard deviation of four measurements and were used to evaluate the maximum pore size. The bubble point pressure was converted to maximum pore size ("calculated maximum pore size") using the following formula: DBP = 4γlvcosθ / PBP where DBP is the calculated maximum pore size, γlv is the surface tension of the liquid, θ is the contact angle of the fluid on the material surface, and PBP is the bubble point pressure. It will be understood by those skilled in the art that the fluid used in the bubble point measurement must wet the surface of the sample. Isopropyl alcohol completely wets the UHMWPE surface, so the contact angle is 0° and the cos(θ) term is 1.

[0095] ATEQ® Airflow The ATEQ® Airflow is a test method that measures the volumetric flow rate of air through a sample. Each sample is sandwiched between two plates, each fitted with a #210 or equivalent O-ring, and a 2.99 cm dia. flow path. 2There are open holes between the O-rings so that a sealed area of ​​1.2 kPa (1.2 psi) is created. The holes in the downstream flow path are crossed by a grid support structure. The air flow rate (L / hr) through each sample was measured using an ATEQ® (ATEQ Corp., Livonia, MI) Premier D Compact Flow Tester or equivalent equipment, applying a pressure differential of 1.2 kPa (12 mbar) across the sample. Results reported are the average and standard deviation of four measurements.

[0096] SEM surface sample preparation method (sample layout 2) All SEM samples were imaged using a Zeiss SUPRA 35VP scanning electron microscope (Zeiss Microscopy, Jena, Germany) at 2.0 keV in secondary electron detection mode.

[0097] DSC measurement Differential scanning calorimetry (DSC) data were collected using a TA Instruments Discovery DSC (TA Instruments, Neucaste, Germany) at -50 °C or between 35 °C and 200 °C at a heating rate of 10 °C / min. For resin samples, approximately 5 mg of powder was placed into a standard pan and lid combination available from TA Instruments. Membrane samples were prepared by punching out 4 mm disks. The 4 mm disks were placed flat in the pan and the lid was crimped to sandwich the membrane disk between the pan and lid. Melting enthalpy data were integrated using a linear integration scheme from 80 °C to 180 °C. Subsequent deconvolution of the melting region was performed using SeaSolve Software's PeakFit software (PeakFit v4.12 for Windows, Copyright 2003, SeaSolve Software Inc.). Standard conditions were used to fit the baseline (after inverting the data to generate a "positive" peak) and the observed data was subsequently decomposed into individual melting components. EXAMPLES

[0098] The following examples were carried out on a laboratory scale, but it should be understood that they can be readily adapted to a continuous or semi-continuous process.

[0099] Example 1a Powder preparation: 100 g of ultra-high molecular weight polyethylene powder having a molecular weight of about 7,000,000 g / mol and an enthalpy of fusion of greater than 190 J / g as measured by DSC, prepared as reported in patent number WO2012053261, was placed in a 2 liter screw cap jar. Isopar™ V (ExxonMobil Chemical Company, Spring, Texas) isoparaffinic hydrocarbon lubricant (60 mL) was added and mixed at room temperature at 30 rpm using a tumbler for 15 minutes. The mixture was preheated to 60° C. prior to calendering.

[0100] Tape calendering process: In a calender, 30.5 cm diameter rolls were preheated to 124°C and the gap between the rolls was set at 0.15 mm. A lubricated polymer was introduced into the gap with a feeder to produce a continuous tape 15.2 cm wide. The tape was opaque, flexible, and approximately 0.17 mm thick.

[0101] Lubricant removal: The tape was extracted and washed with boiling hexane using a Soxhlet extractor for 2 hours, then air-dried at room temperature (approximately 22° C.) in a fume hood.

[0102] Biaxial stretching: Samples were cut from the tape and placed in a Karo IV biaxial stretcher (available from Bruckner Group, GmbH, Siegsdorf, Germany) and simultaneously stretched according to the following process: 1. Preheat the sample to 135°C for 30 seconds. 2. At 135° C.: the tape was stretched at a stretch ratio of 1.5 at 150% / sec in the calender direction and 2.0 at 300% / sec in the transverse direction (perpendicular to the calender). 3. Preheat the sample at 160°C for 15 seconds. 4. At 160° C.: further stretched at a stretch ratio of 4.5 at 0.7% / sec in the calendar direction and 8.0 at 1.4% / sec in the transverse direction.

[0103] A scanning electron micrograph (SEM) of the surface of the expanded UHMWPE membrane taken at 1,000x magnification is shown in Figure 1. A differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the expanded UHMWPE membrane of Example 1a is included in Figure 8.

[0104] The properties of the biaxially stretched membrane are shown in Table 1.

[0105] Example 1b Powder preparation, tape calendering and delubricant were prepared using the methods described in Example 1a.

[0106] Biaxial stretching: The samples were biaxially oriented according to the following steps: 1. Preheat the sample to 135°C for 30 seconds. 2. At 135° C.: the tape was stretched at a stretch ratio of 1.5 at 40% / sec in the calender direction and 2.0 at 80% / sec in the transverse direction (perpendicular to the calender). 3. At 160° C.: Further stretched at 0.7% / sec to a stretch ratio of 2.67 in the calender direction and 2.2% / sec to a stretch ratio of 5.0 in the transverse direction (perpendicular to the calender).

[0107] A scanning electron micrograph (SEM) of the surface of the expanded UHMWPE membrane taken at 1,000x magnification is shown in Figure 2. A differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the expanded UHMWPE membrane of Example 1b is included in Figure 9.

[0108] The properties of the biaxially stretched membrane are shown in Table 1.

[0109] Example 2a Powder preparation, tape calendering and delubricant were prepared using the methods described in Example 1a.

[0110] Biaxial stretching: The sample was biaxially stretched following steps (1-3) outlined in Example 1a, except steps 3 and 4 were performed at 135° C., and step 5 was added. 1. Preheat the sample to 135°C for 30 seconds. 2. At 135° C.: the tape was stretched at a stretch ratio of 1.5 at 150% / sec in the calender direction and 2.0 at 300% / sec in the transverse direction (perpendicular to the calender). 3. Preheat the sample to 135°C for 15 seconds. 4. At 135° C.: Stretched at an additional stretch ratio of 4.5 at 0.7% / sec in the calendar direction and 8.0 at 1.4% / sec in the transverse direction. 5. The stretched film was held at 160°C for 30 seconds.

[0111] A scanning electron micrograph (SEM) of the surface of the expanded UHMWPE membrane taken at 1,000x magnification is shown in Figure 3. A differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the expanded UHMWPE membrane of Example 2a is included in Figure 10.

[0112] The properties of the biaxially stretched membrane are shown in Table 1.

[0113] Example 2b Powder preparation, tape calendering and delubricant were prepared using the methods described in Example 1a.

[0114] Biaxial stretching: The sample was biaxially stretched following steps (1-3) outlined in Example 1b, except step 3 was performed at 135° C. and step 4 was added. 1. Preheat the sample to 135°C for 30 seconds. 2. At 135° C.: the tape was stretched at a stretch ratio of 1.5 at 40% / sec in the calender direction and 2.0 at 80% / sec in the transverse direction (perpendicular to the calender). 3. At 135° C.: Stretched at 0.7% / sec to a stretch ratio of 2.67 in the calender direction and 2.2% / sec to a stretch ratio of 5.0 in the transverse direction (perpendicular to the calender). 4. The stretched film was held at 160°C for 30 seconds.

[0115] A scanning electron micrograph (SEM) of the surface of the expanded UHMWPE membrane taken at 1,000x magnification is shown in Figure 4. A differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the expanded UHMWPE membrane of Example 2b is included in Figure 11.

[0116] The properties of the biaxially stretched membrane are shown in Table 1.

[0117] Comparative example A Powder preparation, tape calendering and lubricant removal were carried out using the methods described in Example 1a. Biaxial orientation was carried out entirely below the melting temperature of the UHWMPE polymer, according to Example 1 of U.S. Pat. No. 9,926,416, without exposure to temperatures above the melting temperature after orientation.

[0118] Biaxial stretching: The sample was biaxially stretched following steps 1-4 outlined in Example 2a, but omitting the post-stretch hold at 160° C. (step 5). 1. Preheat the sample to 135°C for 30 seconds. 2. At 135° C.: the tape was stretched at 150% / sec in the calender direction to a stretch ratio of 1.5 and at 300% / sec in the transverse direction (perpendicular to the calender) to a stretch ratio of 2.0. 3. Preheat the sample to 135°C for 15 seconds. 4. At 135° C.: further stretched at a stretch ratio of 4.5 at 0.7% / sec in the calendar direction and 8.0 at 1.4% / sec in the transverse direction.

[0119] A scanning electron micrograph (SEM) of the surface of the expanded UHMWPE membrane taken at 1,000x magnification is shown in Figure 5. A differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the expanded UHMWPE membrane of Comparative Example A is included in Figure 12.

[0120] The properties of the biaxially stretched membrane are shown in Table 1.

[0121] Comparative example B Powder preparation, tape calendering, and lubricant removal were performed using the methods described in Example 1a. Biaxial orientation was performed entirely below the melting temperature of the UHWMPE polymer, without exposure to temperatures above the melting temperature after orientation, in accordance with Example 1 of U.S. Pat. No. 9,926,416.

[0122] Biaxial stretching: The sample was biaxially stretched following steps 1-4 outlined in Example 2b, omitting the post-stretch hold at 160° C. (step 4). 1. Preheat the sample to 135°C for 30 seconds. 2. At 135° C.: the tape was stretched at a stretch ratio of 1.5 at 40% / sec in the calender direction and 2.0 at 80% / sec in the transverse direction (perpendicular to the calender). 3. At 135° C.: Further stretched at 0.7% / sec to a stretch ratio of 2.67 in the calender direction and 2.2% / sec to a stretch ratio of 5.0 in the transverse direction (perpendicular to the calender).

[0123] A scanning electron micrograph (SEM) of the surface of the expanded UHMWPE membrane taken at 1,000x magnification is shown in Figure 6. A differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the expanded UHMWPE membrane of Comparative Example B is included in Figure 13. The properties of the biaxially stretched membrane are shown in Table 1.

[0124] [Table 1]

[0125] The invention of this application has been described above both generically and with respect to specific embodiments. While the invention has been described in what are believed to be preferred embodiments, various alternatives known to those skilled in the art may be selected within the scope of the generic disclosure. The invention is not otherwise limited, except as set forth in the claims below.

Claims

1. having a molecular weight of at least 2,000,000 g / mol; The enthalpy of fusion is at least 190 J / g; 1. An article comprising a porous polyethylene membrane formed from an ultra-high molecular weight polyethylene (UHMWPE) polymer, The porous polyethylene film is A node and fibril microstructure having a structure of nodes interconnected by fibrils; A first detectable endotherm associated with the UHMWPE polymer in the range of about 139°C to about 143°C; A detectable second endotherm associated with fibrils between 145° C. and 155° C.; and a bubble point of 138 kPa or less, preferably 69.0 kPa or less, more preferably 34.5 kPa or less; An article comprising:

2. The porous polyethylene membrane is 2.99 cm 2 2. The article of claim 1 having an ATEQ® airflow of at least 50 L / hr, preferably at least 500 L / hr, more preferably at least 1000 L / hr at a pressure of 1.2 kPa over a surface area of ​​1.

3. The article of claim 1 or 2, wherein the porous polyethylene membrane has a machine direction (MD) matrix tensile strength of at least 30 MPa.

4. The article of any one of claims 1 to 3, wherein the porous polyethylene membrane has a transverse direction (TD) matrix tensile strength of at least 4 MPa.

5. The article of any one of claims 1 to 4, wherein the film is biaxially oriented.

6. The article of any one of claims 1 to 5, wherein the matrix tensile strength ratio MD:TD is from 0.1:1 to 1:0.

1.

7. The article of any one of claims 1 to 6, wherein the UHMWPE polymer has a molecular weight of from 2,000,000 g / mol to 12,000,000 g / mol.

8. The article of any one of claims 1 to 7, wherein the article is a sheet, a film, a tape, a fiber, a tube, a bead, or a three-dimensional free-standing structure.

9. The article of any one of claims 1 to 8, wherein the porous membrane has a porosity of at least 60%.

10. The article of any one of claims 1 to 9, wherein the membrane has an average thickness of less than 1 mm.

11. The article of any one of claims 1 to 10, wherein the UHMWPE polymer comprises 0.001 mol% to 10 mol% of a comonomer.

12. lubricating an ultra-high molecular weight polyethylene (UHMWPE) polymer having a molecular weight of at least 2,000,000 g / mol and only a single endotherm with a melting enthalpy of at least 190 J / g to form a lubricated polymer; exposing the lubricated UHMWPE polymer to pressure at a temperature below the melting temperature of said UHMWPE polymer to form a tape; stretching the tape at a temperature below the melting temperature of the UHMWPE polymer to form an oriented tape; and stretching the stretched tape at a temperature above the melting temperature of the UHMWPE polymer to form a porous UHMWPE membrane having a structure of nodes interconnected by fibrils; A method comprising:

13. The method of claim 12, wherein the porous UHMWPE membrane has a molecular weight of 2,000,000 to 12,000,000 g / mol.

14. 14. The method of claim 12 or 13, wherein the porous UHMWPE membrane has a first endotherm and a second endotherm at 145°C to 155°C associated with fibrils in the porous UHMWPE membrane and above the melting temperature of the ultra high molecular weight polyethylene polymer.

15. A method according to any one of claims 12 to 14, wherein the porous UHMWPE membrane has a bubble point of 138 kPa or less, preferably 69 kPa or less, more preferably 34.5 kPa or less.

16. The porous UHMWPE membrane is 2.99 cm 2 16. The method of any one of claims 12 to 15, having an ATEQ® air flow of at least 50 L / h, preferably at least 500 L / h, most preferably 1000 L / h at a pressure of 1.2 kPa over a surface area of

17. The method of any one of claims 12 to 16, wherein the tape and oriented tape are biaxially oriented, uniaxially oriented, radially oriented, or a combination thereof.

18. The method of any one of claims 13 to 18, wherein the tape is stretched at a temperature of from 110°C to 135°C.

19. The method of any one of claims 13 to 19, wherein the tape is stretched at a temperature of from 140°C to 170°C.

20. The method of any one of claims 12 to 19, wherein said exposing comprises calendering said lubricated UHMWPE polymer at a temperature below the melting temperature of the UHMWPE polymer to form a tape.

21. The method of any one of claims 12 to 20, further comprising removing lubricant from the tape before stretching.

22. The method of any one of claims 12 to 21, wherein the UHMWPE polymer has a molecular weight of from 5,000,000 g / mol to 12,000,000 g / mol.

23. The method of any one of claims 12 to 22, wherein the UHMWPE membrane has a porosity of greater than 60%.

24. The method of any one of claims 12 to 23, wherein the UHMWPE membrane has a first endotherm associated with the UHMWPE polymer in the range of 139°C to 143°C.

25. The method of any one of claims 12 to 24, wherein the UHMWPE membrane has an average thickness of less than 1 mm.

26. The method of any one of claims 12 to 25, wherein the UHMWPE polymer comprises 0.001 mol% to 10 mol% of a comonomer.

27. 1. A method comprising exposing a lubricated ultra-high molecular weight polyethylene (UHMWPE) polymer having a molecular weight of at least 2,000,000 and a first endotherm having a melting enthalpy of at least 190 J / g to pressure and heat below a first melting temperature of said UHMWPE polymer to form a preform, subsequently stretching said preform at a temperature below the melting temperature of said UHMWPE polymer to form a stretched preform, and then stretching said stretched preform at a temperature above the melting temperature of said UHMWPE polymer to form a porous UHMWPE membrane; The porous UHMWPE membrane has a bubble point of 138 kPa or less, preferably 69.0 kPa or less, more preferably 34.5 kPa or less; The porous UHMWPE membrane is 2.2 cm 2 1.2 kPa pressure over a surface area of ​​at least 50 L / hr, preferably at least 500 L / hr, more preferably at least 1000 L / hr.

28. 28. The method of claim 27, wherein the porous UHMWPE membrane has a second endotherm between 145° C. and 155° C. associated with fibrils within the porous UHMWPE membrane, the second endotherm being above the melting temperature of the UHMWPE polymer.

29. 29. The method of claim 27 or 28, wherein the preform and the stretched preform are biaxially stretched, uniaxially stretched, radially stretched, or a combination thereof.

30. The method of any one of claims 27 to 29, wherein the preform is stretched at a temperature of from about 110°C to about 135°C.

31. The method of any one of claims 27 to 30, wherein the preform is stretched at a temperature of from 140°C to 170°C.

32. The method of any one of claims 27-31, wherein said exposing comprises calendering the lubricated UHMWPE polymer at a temperature below the melting temperature of said UHMWPE polymer to form a preform.

33. The method of any one of claims 27 to 32, including removing lubricant from the preform before stretching.

34. The method of any one of claims 27 to 33, wherein the UHMWPE polymer has a molecular weight of from 2,000,000 g / mol to 12,000,000 g / mol.

35. The method of any one of claims 27 to 34, wherein the UHMWPE membrane has a porosity of greater than 60%.

36. The method of any one of claims 27-35, wherein the UHMWPE membrane has a first endotherm associated with the UHMWPE polymer in the range of 139°C to 143°C.

37. The method of any one of claims 27 to 36, wherein the UHMWPE membrane has an average thickness of less than 1 mm.

38. The method of any one of claims 27 to 37, wherein the UHMWPE polymer comprises 0.001 mol% to 10 mol% of a comonomer.

Citation Information

Patent Citations

  • Production of porous film

    JP2000109586A

  • Method for producing porous articles derived from ultra-high molecular weight polyethylene

    JP2016508535A

  • Paste-processed ultra-high molecular weight polyethylene expanded into high density articles

    JP2024546933A

  • Method for producing ultra-high-molecular-weight polyethylene porous membrane, method for producing ultra-high-molecular-weight polyethylene film, and porous membrane and film produced by said methods

    WO2012029881A1